Linking perceived management support with employees' readiness for change: the mediating role of psychological capital. Issue 1 (2nd January 2017) - Kirrane, Melrona; Lennon, Margaret; O'Connor, Cliodhna; Fu, Na
ABSTRACT: Although the relationship between management support and readiness for change is a well-studied topic, mediating variables in this relationship are rarely examined. This paper presents the findings of an investigation into the mediating role of psychological capital (PsyCap) in the relationship between perceived management support and readiness for change. A questionnaire was administered to employees ( N  = 120) of a public sector organization undergoing a change initiative. Results of structural equation modelling demonstrated that PsyCap partially mediated the relationship between management support and employees' readiness for change. This indicates that employees' responses to change are shaped by both their personal psychological resources and their perceptions of the organizational environment. The findings offer a platform for positive future developments in research and practice.